1998
DOI: 10.1161/01.res.83.8.832
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Upregulates the Expression of Matrix Metalloproteinases in Vascular Smooth Muscle Cells

Abstract: Vascular endothelial growth factor (VEGF) is a critical regulator of angiogenesis that stimulates proliferation, migration, and proteolytic activity of endothelial cells. Although the mitogenic activity of VEGF is endothelial cell specific, recent reports indicate VEGF is able to stimulate chemotaxis and tissue factor production in monocytes. VEGF-stimulated activity in monocytes is mediated by the VEGF receptor flt-1. The purpose of the present study was to investigate the effects of VEGF on another major cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
234
0
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(251 citation statements)
references
References 54 publications
8
234
0
9
Order By: Relevance
“…ANOVA yielded P = <0.0001 for all except bFGF (NS). * and # indicate P < 0.05 (Tukey post-test) versus control and trained, respectively (Wang and Keiser 1998). The role of VEGF in relation to the exercise-induced modiWcations of skeletal muscles, the mode of capillary growth (by intussusceptions rather than sprouting) and the mechanical forces involved have been thoroughly discussed by Brown and Hudlicka (2003).…”
Section: Discussionmentioning
confidence: 99%
“…ANOVA yielded P = <0.0001 for all except bFGF (NS). * and # indicate P < 0.05 (Tukey post-test) versus control and trained, respectively (Wang and Keiser 1998). The role of VEGF in relation to the exercise-induced modiWcations of skeletal muscles, the mode of capillary growth (by intussusceptions rather than sprouting) and the mechanical forces involved have been thoroughly discussed by Brown and Hudlicka (2003).…”
Section: Discussionmentioning
confidence: 99%
“…9 Activation of VEGFR-1 by VEGF in endothelial cells lacking VEGFR-2 does not induce cell proliferation. 9 VEGFR-1 plays an important role in modulating the activities of VEGFR-2 37,38 and the circulating levels of VEGF, in regulating extracellular matrix proteolytic activity, 39 and in controlling the release of nitric oxide by endothelial cells. 9 These aspects are mainly due to the different signal transduction cascades induced by VEGFR-1 and VEGFR-2; and specifically, for cell proliferation, to the activation of mitogen-activated protein kinase (MAPK) only by VEGFR-2.…”
Section: Discussionmentioning
confidence: 99%
“…16,[38][39][40] Our results indicated that in DU-145 cells MMP-9 and MMP2 levels did not change upon incubation in hypoxia or with the addition of GA to hypoxic-treated cells 18 used breast cancer cells to demonstrate in certain hypoxic cell lines in fact lead to increased MMP-9 but not MMP-2 levels. However, they kept their cells in hypoxia for 24 h. Other studies have demonstrated that VEGF can upregulate MMP-9 via its activation of VEGF receptors in different cell lines.…”
Section: Inhibition Of Hif-1a By Geldanamycinmentioning
confidence: 94%